HUBUNGAN DUKUNGAN KELUARGA DAN PENGARUH TEMAN SEBAYA DENGAN PERILAKU HYGIENE MENSTRUASI PADA REMAJA PUTRI DI SMP NEGERI 2 CIGUDEG KABUPATEN BOGOR - Devia Febriani (2020)
Menstrual hygiene behavior is the behavior of a person to maintain and maintain the cleanliness of the reproductive organs during menstruation in order to avoid reproductive tract infections. This study aims to analyze the relationship of family support and peer influence with menstrual hygiene behavior in adolescent women in SMP Negeri 2 Cigudeg Kabupaten Bogor, this type of research is a descriptive analytic study with a cross-sectional approach and analyzed with the Chi-Square test, the population in this study is adolescent women in SMP Negeri 2 Cigudeg Kabupaten Bogor with a sample of 90 people, the sampling technique uses stratified random sampling, the results of this study obtained from this analysis there is no relationship of family support with menstrual hygiene behavior in adolescent girl in SMP Negeri 2 Cigudeg Kabupaten Bogor (p=0,414) and there is a relationship of peer influence with menstrual hygiene behavior in adolescent girl in SMP Negeri 2 Cigudeg Kabupaten Bogor (p=0,03). Suggestions need to disseminate information about maintaining reproductive hygiene for adolescents, routinely bringing health workers to school to provide counseling on adolescent reproductive health, especially regarding hygiene during menstruation.